The Wider Island of Pelops Studies on Prehistoric Aegean Pottery in Honour of Professor Christopher Mee. - Smith, David Michael (Archaeopress, 2023)
This volume explores the myriad ways in which pottery was created, utilized, and experienced in the prehistoric Aegean, across a period of more than 4000 years between the Middle Neolithic and the Early Iron Age transition.